Confronting the environmental consequences of the Green Revolution in Asia - Pingali, Prabhu L.; Rosegrant, Mark W. (International Food Policy Research Institute, 1994)
Intensive double or triple monocropping of rice has caused degradation of the paddy micro environment and reductions in rice yield growth in many irrigated areas in Asia. Problems include increased pest infestation, mining of soil micronutrients, reductions in nutrient-carrying capacity of the soil, build-up of soil toxicity, and salinity and waterlogging. Emerging sustainability problems in intensive rice agriculture show the need for a greater understanding of the physical, biological and ecological consequences of agricultural intensification and greater research attention to long term management of the agricultural resource base.